Identification and prioritization of construction waste management strategies using an integrated FANP-DEMATEL/SWOT model in Tehran metropolis, Iran - Hossein Aligholizadeh; Saeed Motahari; Maryam Farahani; Hasan Samadyar (Anthropogenic Pollution)
The purpose of the current work was to develop strategies suitable for the construction waste management for construction waste processing, recycling or landfilling plants in Tehran metropolis, Iran. This integrated methods study was of an applied type with an exploratory approach, which used a FANP-DEMATEL combined model as one of the most appropriate strategic planning methodologies. Thus, the environment of Tehran waste management organization (TWMO) was evaluated by preparing a SWOT matrix consisting of 10 strengths (S), 12 weaknesses (W), 9 opportunities (O), and 7 threats (T). According to the results, the TWMO was positioned in the WT box (IFE: 2.45 and EFE: 2.33), indicating the necessity of adopting a defensive strategy as the best priority. On the other hand, the FANP-DEMATEL technique also confirmed the accuracy of WT strategies with a score of 12.627. Results shown that the best determined WT strategy was “Preventing mixing or separating waste at the source for easier recycling at the plant site" (Weighting factor: 0.9). These findings showed the importance of the proposed strategy for the growth and success of construction and demolition waste management in Tehran.